Comprehensive metabolite profile of Chlorella vulgaris and metabolic signature of its immunostimulating effect in Nile tilapia [Oreochromis niloticus (Linnaeus, 1758)] - Pantami, Hamza Ahmed (2020)
Chlorella vulgaris is a green, single-celled, spherical freshwater microalga belonging to the family Chlorellaceae of the division Chlorophyta. C. vulgaris is currently used as food supplement and medicinal agent due to its carotenoids, chlorophylls and proteins content. Chlorella vulgaris is incorporated in fish feed as a growth and immune stimulant. Tilapia is one of the most important cultured fish species with numerous advantages, contributing more than USD 10 billion to the world’s seafood market annually. Despite the important features of tilapia, disease outbreaks tend to cause massive mortalities in fish farms which impose serious negative impact to economies worldwide. Most tilapia mortalities were reported as a resultant stress due to overcrowding coupled with bacterial infection. Streptococcus agalactiae is one of the most virulent bacteria causing most of tilapia mortalities recently. The use of immunostimulants like microalgal supplementation in fish feed holds a promising future in mitigating tilapia fish disease. Nevertheless, the common amounts used (≥12%) in this practice is considered uneconomical by fish farmers, considering the high price of microalgal biomass procurement. In addition, scientific reports regarding the association of metabolites with pathways involved in the stimulation of immune system of tilapia fish (Oreochromis niloticus) exerted by consumption of C. vulgaris are still limited. Hence, the main aim of this study was to investigate the immunestimulating role of bioactive metabolites from C. vulgaris on the tilapia fish at lower concentrations using proton nuclear magnetic resonance (1H-NMR) metabolomics approach. The first part of the study dealt with the characterization of the metabolite composition of the cultured samples of C. vulgaris via 1H-NMR, gas chromatography mass spectrometry (GCMS) lipid analysis and liquid chromatography mass spectrometry (LC-MS/MS) analysis. 1H-NMR data obtained from six different organic solvent extracts were used to establish the general metabolite profile and their variation was determined via multivariate data analysis (MVA) and complemented with mass spectrometric data. LC-MS/MS analysis led to the profiling of carotenoids comprising of violaxanthin, neoxanthin, lutein, β-carotene, vulgaxanthin I, astaxanthin and antheraxanthin along with other metabolites such as amino acids, vitamins, and chlorophylls. The metabolite compositions indicated that C. vulgaris could serve as a good source of dietary nutrients. Fatty acid profile of C. vulgaris revealed that it was rich in omega-6,7,9 and 13 fatty acids, with dominance of omega-6 fatty acids (>60% of the total fatty acids). Besides, the main fatty acids were those of C16-C18 (>92%), suggesting high potential for utilization of C. vulgaris in biodiesel production. In addition, 48 lipids were putatively identified via Molecular Networking of the LCMS/ MS data which include glycosphingolipids, phosphoethanolamines, phosphoserines and phosphocolines. The second part of the study determined the safety of C. vulgaris concentration as a fish feed at 500 mg/kg body weight (bw) by assessing several immune parameters. The immune parameters assessed were serum lysozyme activity (SLA), serum bactericidal activity (SBA), phagocytosis activity (PHA), respiratory burst activity (RBA) and lymphocyte proliferation (LP). There was no mortality recorded nor sign of organ lesion observed throughout the assessment period. The immune parameters assessed at 5%, 2.5%, 1.25% and 0.625% showed significant improvement in PHA, RBA and LP with 1.25% (125 mg/kg bw) been the best dose for future use economically. The third part of the present study correlated the immune parameters with the primary metabolite composition of the serum and spleen of the tilapia fish using 1H-NMR metabolomics. Metabolites such as choline, glucose, riboflavin, stearic acid, linolenic acid, leucine, histamine, proline, glycine, and alanine levels in tilapia fish fed with C. vulgaris exhibited improvements compared to the control tilapia fish, with reduction in the level of glutamic acid. The linoleic acid metabolism had the highest impact factor, followed by riboflavin metabolism, D-glutamine and D-glutamate metabolism and starch and sucrose metabolism, with impact factors of 1.00, 0.50, 0.50 and 0.39, respectively. Chlorella vulgaris incorporation into fish diet at a concentration of 125 mg/kg bw showed to be considerably enough in improving tilapia immune parameters and was used for the prophylaxis studies in the last part of the research study for economic considerations. The last part of the study showed that the immune stimulation by C. vulgaris was sustained even after challenging of the tilapia fish with a virulent bacterium, Streptococcus agalactiae concentration of 108 CFUmL-1 for 7 days. This finding agreed with the 90% survival rate of the fish fed with C. vulgaris (CVC) as compared to the 13% survival rate of the control fish (CF) and significantly higher metabolite fold changes in CVC in comparison with CF. This research provides scientific evidence for utilization of C. vulgaris as an immune stimulant for tilapia fish. On the other hand, 1H-NMR metabolomics is a sound methodology for the identification of biomarkers in immune system-stimulated tilapia fish. To the best of our knowledge, the present study was the first investigation that proposed the biomarkers along with associated pathways involved in immune stimulation of tilapia fish consuming C. vulgaris. The findings could pave a way for development of efficient strategies in mitigating fish diseases in aquaculture practice.